Skin-focused repetitive behavioral disorder. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2021)
In DSM-5 (5th edition of the Diagnostic and Statistical Manual of Mental Disorders) obsessive compulsive disorder (OCD) is no longer part of anxiety disorders but becomes a separate chapter along with related disorders, such as compulsive excoriation of the skin, trichotillomania, nail biting, etc. OCD is characterized by obsessions, that is thoughts that are perceived as unpleasant by the subject, and by compulsions, that is, repetitive actions implemented by the subject to alleviate the discomfort caused by the obsessions. However, the compulsions do not eliminate the obsessions that are repeated on time. Compulsive actions are preceded by a feeling of progressive excitement, agitation and followed by a feeling of momentary relief or pleasure but also by a sense of guilt. It should be noted that obsessive-compulsive disorder has a very different severity: it ranges from mild, very frequent (2) forms of onychophagy, often familial and therefore due to imitation of what the subject sees a parent doing, to severe forms with repercussions on social life and quality of life, which therefore require treatment. The most commonly used drugs in this field are selective serotonin reuptake inhibitors, clomipramine and N-acetylcysteine (1, 3, 4). However, these drugs have yielded clinical results below their theoretical expectations (4). Cognitive behavioral therapy seems more effective and in particular habit reversal therapy (5), which includes several stages, in particular awareness, stimulus control, competitive response, relaxation exercises and social support. In the first stage, the patient must become aware of his/her problem and of the stimuli that generate the repetitive reaction; in this stage the patient also learns to monitor and record the moments of his/her repetitive behavior. Then the patient must learn to avoid and control the stimuli that cause his/her repetitive actions. He/she must then learn to perform relaxation exercises that reduce agitation and stress. It is then necessary to suggest to the patient competitive responses to stimuli capable of provoking compulsive actions: for example, squeeze the fists keeping the arms extended at the sides, clap hands, sit on top of his/her hands, etc.; finally, the presence of a support person is required who rewards the subject when he correctly performs the listed stages and who discusses with him/her any failures in carrying them out. We have presented this case because we have not found compulsive actions in the literature such as those implemented by our patient and to highlight the important psycho-social consequences of such actions.